Clinical and neurophysiological effects of manual acupuncture for upper-limb motor dysfunction after ischemic stroke: a three-arm randomized controlled trial - Yu Min; Zhendong Huang; Ju Sun; Zetong Peng; Hongli Guan; Yuying Gong; Kaifeng Guo (Frontiers in Neurology, 2026)
Background Upper-limb motor dysfunction is common after ischemic stroke. Evidence separating acupuncture effects from nonspecific needling effects remains limited. This study evaluated manual acupuncture combined with conventional rehabilitation in patients with poststroke upper-limb motor dysfunction. Methods This single-center, assessor-blinded, three-arm randomized trial enrolled and randomized 84 patients with unilateral upper-limb impairment within 3 months after ischemic stroke. Participants were assigned 1:1:1 to conventional rehabilitation alone, sham acupuncture plus conventional rehabilitation, or manual acupuncture plus conventional rehabilitation for 4 weeks. All randomized participants were included in the full analysis set. Manual acupuncture was applied at GV20, GV14, LI11, PC6, ST36, and SP6 with manipulation to elicit de qi. Sham acupuncture used superficial nonacupoint needling without manipulation. The primary outcome was change in Fugl-Meyer Assessment of the Upper Extremity (FMA-UE) score. Secondary outcomes included Modified Barthel Index (MBI), absolute surface electromyography (sEMG) RMS amplitudes during passive stretch and voluntary contraction, functional near-infrared spectroscopy-measured cortical activation and resting-state functional connectivity, and adverse events. Results Manual acupuncture produced greater FMA-UE improvement than conventional rehabilitation and sham acupuncture, with between-group differences of 9.64 points (95% CI, 5.62 to 13.66; Bonferroni-adjusted p < 0.001) and 8.57 points (95% CI, 4.55 to 12.59; Bonferroni-adjusted p < 0.001), respectively. MBI scores also improved more in the manual acupuncture group, with differences of 7.32 points versus conventional rehabilitation (95% CI, 1.52 to 13.13; Bonferroni-adjusted p = 0.040) and 11.29 points versus sham acupuncture (95% CI, 5.48 to 17.09; Bonferroni-adjusted p < 0.001). Manual acupuncture was associated with larger increases in unnormalized biceps brachii and triceps brachii RMS amplitudes during voluntary contraction. Functional near-infrared spectroscopy showed greater ipsilesional prefrontal cortex and primary motor cortex activation after false discovery rate correction, with altered prefrontal and sensorimotor connectivity. Sham acupuncture did not differ significantly from conventional rehabilitation for most outcomes. Three mild cases of subcutaneous bleeding occurred, with no serious adverse events. Conclusion Manual acupuncture combined with conventional rehabilitation improved upper-limb motor function and activities of daily living after ischemic stroke. These effects were accompanied by larger increases in proximal-muscle RMS amplitudes during voluntary contraction and by fNIRS-based changes in cortical activation and functional connectivity. Clinical trial registration https://itmctr.ccebtcm.org.cn/ , Identifier, ITMCTR2025002121.